Pengembangan Profesionalisme Guru Sebagai Salah Satu Upaya dalam Meningkatkan Mutu Pendidikan - Widya Purnama (JPT : Jurnal Pendidikan Tematik, 2024)
The aim of this research is to determine the professionalism of teachers as educators in order to improve the quality of education along with efforts to increase this professionalism. The research method used is a qualitative method with a descriptive approach sourced from literature studies. This research uses a qualitative method with a descriptive approach sourced from literature studies. The qualitative descriptive method is a type of research that can produce information in the form of notes and descriptive data sourced from the text being studied. Data collection techniques are carried out by reading and reviewing various accurate literature sources, be they books or existing research journals. The results of this research are: (1) Development of teacher professionalism. Professional development is teacher activities in the application of science and knowledge, technology and skills to improve quality, both for the teaching and learning process and the professionalism of other education staff. (2) Teacher professionalism. Professionalism is a performance quality and at the same time a demand for professional behavior in carrying out their duties. Consequently, teachers as professionals are required to be able to work within the corridors of professionalism. and (3) Quality of education. The general definition of quality is the overall description or characteristics of goods or services that demonstrate their ability to satisfy expected needs.